Bacteria and Metabolic Potential in Karst Caves Revealed by Intensive Bacterial Cultivation and Genome Assembly - Zhu, Hai-Zhen (Appl Environ Microbiol, 2021)
Karst caves are widely distributed subsurface systems, and the microbiomes therein are proposed to be the driving force for cave evolution and biogeochemical cycling. In past years, culture-independent studies on the microbiomes of cave systems have been conducted, yet intensive microbial cultivation is still needed to validate the sequence-derived hypothesis and to disclose the microbial functions in cave ecosystems. In this study, the microbiomes of two karst caves in Guizhou Province in southwest China were examined. A total of 3,562 bacterial strains were cultivated from rock, water, and sediment samples, and 329 species (including 14 newly described species) of 102 genera were found. We created a cave bacterial genome collection of 218 bacterial genomes from a karst cave microbiome through the extraction of 204 database-derived genomes and de novo sequencing of 14 new bacterial genomes. The cultivated genome collection obtained in this study and the metagenome data from previous studies were used to investigate the bacterial metabolism and potential involvement in the carbon, nitrogen, and sulfur biogeochemical cycles in the cave ecosystem. New N(2)-fixing Azospirillum and alkane-oxidizing Oleomonas species were documented in the karst cave microbiome. Two pcaIJ clusters of the β-ketoadipate pathway that were abundant in both the cultivated microbiomes and the metagenomic data were identified, and their representatives from the cultivated bacterial genomes were functionally demonstrated. This large-scale cultivation of a cave microbiome represents the most intensive collection of cave bacterial resources to date and provides valuable information and diverse microbial resources for future cave biogeochemical research. IMPORTANCE Karst caves are oligotrophic environments that are dark and humid and have a relatively stable annual temperature. The diversity of bacteria and their metabolisms are crucial for understanding the biogeochemical cycling in cave ecosystems. We integrated large-scale bacterial cultivation with metagenomic data mining to explore the compositions and metabolisms of the microbiomes in two karst cave systems. Our results reveal the presence of a highly diversified cave bacterial community, and 14 new bacterial species were described and their genomes sequenced. In this study, we obtained the most intensive collection of cultivated microbial resources from karst caves to date and predicted the various important routes for the biogeochemical cycling of elements in cave ecosystems.